DIAGNOSIS OF FULMINANT MYOCARDITIS: CLINICAL APPROACH AND ADVANCED METHODS - Zancan, Luiza Favaro; de Macedo, Ryan Rafael Barros; Baltazar Júnior, Orlando; Albino, Raiany Stephanie; Estrela, Sillas Abrantes; Louzada, Rafael Cardoso; da Silva, Edvania da Paz; Carneiro, Derouchette Ângela da Paz; Costa, Fernando Gomes; dos Santos, José Ricardo; Seabra, Lucas dos Anjos; Gross, Martina Bergmann (Seven Editora, 2026)
Acute myocarditis (AM), a recently onset cardiac inflammation, presents with heterogeneous clinical manifestations, ranging from mild symptoms to high-risk cardiac conditions with severe heart failure, refractory arrhythmias, and cardiogenic shock. The diagnosis of AM is evolving, moving from a definitive diagnosis based on histological evidence of inflammatory infiltrates in cardiac tissue to a provisional diagnosis, corroborated by elevated high-sensitivity troponin associated with specific findings on cardiac magnetic resonance imaging (CMR). As with other medical conditions, a risk-based approach should be promoted to identify the most severe cases of acute myocarditis (AM) that require appropriate treatment protocols, including early recognition, transfer to tertiary centers, aggressive circulatory support with inotropes and mechanical devices, histological confirmation, and eventual immunosuppressive therapy. Despite improvements in the recognition and treatment of fulminant myocarditis (FM), including the wider use of promising mechanical circulatory support devices, severe forms of the disease still present a poor prognosis (AMMIRATI, E. et al., 2022).DOI: https://doi.org/10.56238/sevened2026.002-005